Vascular Malformations of the Orofacial Region - Daya K Jangam; Mohammed Nasiruddin (Wolters Kluwer Medknow Publications, 2010)
Vascular malformations are the benign lesion of the blood vessels or vascular elements and are considered errors of vascular morphogenesis, displaying abnormal dilatations, and channels but no increased cell turnover. Vascular malformations are always present at birth and enlarge in proportion to the growth of the child- They do not involute and remain throughout the patient's life. 1 These lesions occur with equal sex predilection and do not favor any races. Vascular lesions of the face are not very common Most of the oral and oropharyngeal lesions tend to occur in the tongue and the floor of the mouth. 2 In most cases, the diagnosis of vascular malformations is based on clinical evaluation Here a case report is presented of 16-year-old male patient with vascular malformation of the orofacial region. The clinical presentation, radiological finding are discussed with emphasis on recent advances for diagnosis of the same.